Pengaruh kompetensi dan motivasi terhadap kinerja pengrajin sarung sutera mandar Desa Karama Kecamatan Tinambung Kabupaten Polewali Mandar - lulu ilhikmah; Arifhan Ady Dj; Awal Novitanto Bahasoan; Nur Fitriani (Universitas Sulawesi Barat, 2023)
This study's objective was to ascertain how competence and motivation affected the output of the artisans who make Mandar Silk Sarongs in Karama Village, Tinambung District, and Polewali Mandar Regency. The weavers of Karama Village were among the 40 respondents that were sampled for this study using the SPSS method. In this study, both primary and secondary data were utilised. The research sample was given questionnaires as part of the data collection process. In this study, the t test analysis was utilized to test. The findings of this study show that motivation and competence both have positive and significant effects on weavers' performance in Karama Village, Tinambung District, Polewali Mandar Regency.Keywords: Competence, Motivation and Performance